The Image of a Child in Uzbek and English Paremiology - Jobirkhan, Najmiddinov; Sherzod, Samandarov (Pindus Journal of Culture, Literature, and ELT, 2022)
The article is aimed to analyze the block of Uzbek and English proverbs in comparative aspect of extralinguistics – the problem of language and culture. The reasons of non-coincidence in their semantics are connected with the peculiarities of national culture. The paper touches upon the concept “child” as a family member by means of proverbial level.